Spatio-temporal patterns in coral reef composition and function across an altered environmental gradient: A 15-year study in the Caribbean - Briand, Julia K.; Guzmán, Hector M.; Sunday, Jennifer M. (Frontiers in Marine Science, 2023)
Coral species, which function to build the framework structure of reef ecosystems, vary across sheltered to exposed environmental gradients. For centuries, conditions in sheltered environments that impact lagoonal reefs have been altered by local anthropogenic disturbances, while conditions in exposed environments that impact forereefs have largely buffered the effects of local anthropogenic disturbances. Yet, bleaching events induced by global anthropogenic disturbances challenge how we predict changes in reef composition and function across environmental gradients. Here, we quantify spatio-temporal variation in the composition and function of 11 coral reefs across sheltered to exposed environmental conditions over 15 years and 3 bleaching events in Bocas del Toro, Panama. We find that the composition and function of lagoonal reefs and forereefs were distinct and shaped by an environmental gradient altered by anthropogenic disturbance. Lagoonal reefs lacked major reef-building species and experienced greater losses in coral species and diversity over time. Although only lagoonal reefs changed in coral species composition, both lagoonal reefs and forereefs became functionally similar over time. Our findings indicate that lagoonal reefs may be less resilient to global environmental change than forereefs due to long-term effects of local anthropogenic disturbances. Additionally, increasing global anthropogenic disturbances might lead to the homogenization of reef function, as reefs adapt to novel environmental conditions.